A Comparison of Co-expression Networks in Silk Gland Reveals the Causes of Silk Yield Increase During Silkworm Domestication - Zhou, Qiu-Zhong; Fu, Ping; Li, Shu-Shang; Zhang, Chang-Jiang; Yu, Quan-You; Qiu, Chuan-Zhen; Zhang, Hong-Bo; Zhang, Ze (Frontiers in Genetics, 2020)
Long-term domestication and breeding selection have led to that silk yield of the domestic silkworm (Bombyx mori) have increased several times higher than that of its wild ancestor (B. mandarina). However, little is known about the molecular mechanisms of silk yield increase during silkworm domestication. Based on dynamic patterns of functional divergence in silk gland between the domestic and wild silkworms, we found that at early and intermediate stages of silk gland development, the up-regulated genes of the domestic silkworm mainly include DNA integration, nucleic acid binding and transporter activity, which is related to division and growth of cell. This has led to that posterior silk gland (PSG) of the domestic silkworm has significantly more cells ("factories" of fibroin protein synthesis) than that of wild silkworm. At the late stage of silk gland development, the up-regulated genes in the domestic silkworm are enriched in protein processing and ribosome pathways, suggesting that protein synthesis efficiency is greatly improved during silkworm domestication. The synthetic capacity of fibroin proteins of the domestic silkworm has increased, however, the synthetic capacity of sericin proteins has decreased relative to wild silkworm. This reflects that the domestic and wild silkworms have been under different selection pressures. Importantly, we found that the network co-expressed with silk-coding genes for the domestic silkworm is much larger than that for wild silkworm. Furthermore, much more genes co-expressed with silk-coding genes in the domestic silkworm have been subject to artificial selection than those in wild silkworm. Our results revealed that increase in silk yield during silkworm domestication is involved in improvement of a biological system which includes not only expansion of "factories" (cells of PSG) of protein synthesis but also high expression of silk-coding genes as well as silk production related genes such as biological energy, transport, and ribosome pathway genes.